2019
DOI: 10.1038/s41467-019-10421-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient base editing for multiple genes and loci in pigs using base editors

Abstract: Cytosine base editors (CBEs) enable programmable C-toT conversion without DNA doublestranded breaks and homology-directed repair in a variety of organisms, which exhibit great potential for agricultural and biomedical applications. However, all reported cases only involved C-toT substitution at a single targeted genomic site. Whether C-toT substitution is effective in multiple sites/loci has not been verified in large animals. Here, by using pigs, an important animal for agriculture and biomedicine, as the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 48 publications
3
65
1
Order By: Relevance
“…By applying various chemical modifications to ABE mRNA and guide RNA, we successfully engineered an RNA-encoded base editing system. Although previous reports show that unmodified cytidine base editor mRNA and guide RNA could effectively edit embryos and oocytes 14,15 , our data show that unmodified ABE mRNA does not effectively express in HEK293T cells and unmodified guide RNA cannot mediate efficient editing in somatic cell culture. This might be because unmodified mRNA and guide RNA are not stable and will quickly undergo degradation after being delivered to cell culture.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…By applying various chemical modifications to ABE mRNA and guide RNA, we successfully engineered an RNA-encoded base editing system. Although previous reports show that unmodified cytidine base editor mRNA and guide RNA could effectively edit embryos and oocytes 14,15 , our data show that unmodified ABE mRNA does not effectively express in HEK293T cells and unmodified guide RNA cannot mediate efficient editing in somatic cell culture. This might be because unmodified mRNA and guide RNA are not stable and will quickly undergo degradation after being delivered to cell culture.…”
Section: Discussioncontrasting
confidence: 98%
“…Microinjection of cytidine base editor mRNA and in vitro transcribed guide RNA can introduce effective base editing in mouse embryo or pig oocyte 14,15 , suggesting the potential of using RNA-encoded base editors to mediate editing. However, the editing efficiency mediated by RNA-encoded ABE system has not been studied in somatic cells, and its application potential and delivery method have not been addressed.…”
mentioning
confidence: 99%
“…For higher C-to-T editing efficiency, rA1 was replaced by other types of APOBEC deaminases, which also expands the editing scope [50,62]. For instance, conjugating human APOBEC3A (hA3A) in CBEs can efficiently edit cytosines in highly methylated regions and in the GpC dinucleotide content [63][64][65][66][67]. Furthermore, fusing engineered and/or in vitro evolved APOBEC effectors (e.g., rA1-YE1, rA1-YEE, hA3A-Y130F, hA3A-Y132D, eA3A and evoA1) in CBEs can narrow the base editing window (a context region within gRNA target site in which all cytosines can be potentially converted to thymines) to reduce unintended bystander mutations (unintended C-to-T changes within editing windows) and to diversify editing scopes for C-to-T changes [63,[68][69][70].…”
Section: Adopting Naturally Existing Cytidine Deaminase Effector For mentioning
confidence: 99%
“…Furthermore, a study reported that CBEs efficiently induced C-to-T conversions of triple genes simultaneously, including RAG1, RAG2, and IL2RG, or DMD, TYR, and LMNA. These findings will help to accelerate the generation of animal models with multiplex point mutations and studies in gene therapies of genetic diseases [101] . The pig model with RAG1, RAG2, and IL2RG mutations lacked B cells, T cells, and NK cells, providing a great prospect for xenotransplantation.…”
Section: Base Editor Mediated Precise Genetic Modificationsmentioning
confidence: 97%